Sodium renders endothelial cells sticky for red blood cells - Oberleithner, Hans; Wälte, Mike; Kusche-Vihrog, Kristina (Frontiers in Physiology, 2015)
Negative charges in the glycocalyx of red blood cells (RBC) and vascular endothelial cells (EC) facilitate frictionless blood flow through blood vessels. Na+ selectively shields these charges controlling surface electronegativity. The question was addressed whether the ambient Na+ concentration controls RBC-EC interaction. Using atomic force microscopy (AFM) adhesion forces between RBC and endothelial glycocalyx were quantified. A single RBC, mounted on an AFM cantilever, was brought in physical contact with the endothelial surface and then pulled off. Adhesion forces were quantified (i) after enzymatic removal of negative charges in the glycocalyx, (ii) under different ambient Na+ and (iii) after applying the intracellular aldosterone receptor antagonist spironolactone. Removal of negative surface charges increases RBC-EC interaction forces. A stepwise increase of ambient Na+ from 133 to 140 mM does not affect them. However, beyond 140 mM Na+ adhesion forces increase sharply (10% increase of adhesion force per 1 mM increase of Na+). Spironolactone prevents this response. It is concluded that negative charges reduce adhesion between RBC and EC. Ambient Na+ concentration determines the availability of free negative charges. Na+ concentrations in the low physiological range (below 140 mM) allow sufficient amounts of vacant negative charges so that adhesion of RBC to the endothelial surface is small. In contrast, Na+ in the high physiological range (beyond 140 mM) saturates the remaining negative surface charges thus increasing adhesion. Aldosterone receptor blockade by spironolactone prevents Na+ induced RBC adhesion to the endothelial glycocalyx. Extrapolation of in vitro experiments to in vivo conditions leads to the hypothesis that high sodium intake is likely to increase the incidence of thrombotic events.